2017
DOI: 10.1111/tpj.13526
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of retrotransposons, DNA transposons and genes in sugar beet (Beta vulgaris L.)

Abstract: The methylation of cytosines shapes the epigenetic landscape of plant genomes, coordinates transgenerational epigenetic inheritance, represses the activity of transposable elements (TEs), affects gene expression and, hence, can influence the phenotype. Sugar beet (Beta vulgaris ssp. vulgaris), an important crop that accounts for 30% of worldwide sugar needs, has a relatively small genome size (758 Mbp) consisting of approximately 485 Mbp repetitive DNA (64%), in particular satellite DNA, retrotransposons and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 71 publications
9
34
1
1
Order By: Relevance
“…Previous studies have investigated histone modifications and siRNA levels in plant cell suspension cultures in vitro (Tanurdzic et al ., ). Genomewide DNA methylation analysis in leaves and leaf‐derived callus exhibited a differential methylation in tissue culture (Vining et al ., ; Zakrzewski et al ., ). In this study, we revealed the effects of the epigenome on the cotton tissue culture process in the callus, somatic embryos and several regenerated plants through DNA methylation, RNA‐Seq, sRNA‐Seq and ChIP‐Seq analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have investigated histone modifications and siRNA levels in plant cell suspension cultures in vitro (Tanurdzic et al ., ). Genomewide DNA methylation analysis in leaves and leaf‐derived callus exhibited a differential methylation in tissue culture (Vining et al ., ; Zakrzewski et al ., ). In this study, we revealed the effects of the epigenome on the cotton tissue culture process in the callus, somatic embryos and several regenerated plants through DNA methylation, RNA‐Seq, sRNA‐Seq and ChIP‐Seq analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Sugar beet (B. vulgaris) is one of the most important crops around the world for sugar production and is also an important plant resource for biomass energy and animal feed (Dohm et al, 2014;Zakrzewski et al, 2017). Thus, it is highly desirable to identify valuable genes affecting agronomically relevant traits in sugar beet plants.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar beet (B. vulgaris) is an important crop for sugar production, biomass energy and animal feed (Dohm et al, 2014;Zakrzewski et al, 2017). Thus, it is highly important to carry out genomic studies in sugar beets.…”
Section: Application Of the Bnyvv-based Vector For Expression And Submentioning
confidence: 99%
“…In contrast to that, plant genomes have additional CHG and CHH methylation (H = adenine, thymine or cytosine). These last two correlate with the suppression of transposon activity [17], mobile genetic elements that can change their The subsequent polymerase chain reaction (PCR) translates uracil into thymine. During sequencing, this base pair shift causes cytosine/thymine-polymorphism, which can be quantified and interpreted as proportion of the original methylation at a specific site through the comparison of reads with the original strand or a reference genome ( Figure 2).…”
Section: Figurementioning
confidence: 99%
“…In contrast to that, plant genomes have additional CHG and CHH methylation (H = adenine, thymine or cytosine). These last two correlate with the suppression of transposon activity [17], mobile genetic elements that can change their A disadvantage of WGBS is that bisulfite sequencing cannot distinguish between 5hmC and 5mC. The 5hmC is described as the dynamic DNA modification associated with the DNA demethylation process [12] in animals.…”
Section: Figurementioning
confidence: 99%